O uso de gírias nos discursos em Libras pelo povo surdo: um estudo de caso na comunidade surda de Manaus. - Flexa, José Carlos Gonçalves (Brasil, 2023)
The use of slang, in the city of Manaus, in Libras speeches by the Deaf People, shows language put into practice in the area and the flexibility that the language has. There is a lack of both information and materials focusing on events related to Libras, such as articles, publications and books, as a source of research. This research may also provide a clearer understanding of how the relationship between language, culture and deaf identities takes place. Understanding how social groups behave in certain contexts through the use of Libras can lead to reflections on the different levels of registration, as well as practical applications of teaching Libras and other actions involving deaf culture and sign language. From this we raise the following question: Is slang widely disseminated in the Deaf community? General objective of the research is to analyze the use of slang in Sign Language speeches of the deaf community in the city of Manaus. As a methodological procedure, Bakhtin's dialogical analysis (1997) was used in deaf speeches in Manaus. This work dialogues with some theorists such as: Preti (2000 and 2013), Gesser (2009), Perlin (1980 and 2004), Bakhtin (1997), Freire (2017), among others. Thinking about culture is aligned with the deaf community, thus also showing challenges in the Libras area through this research, providing appropriate reflections in the context on past and present slang. Through the course of this work, we were able to highlight some slang signs belonging to the speeches of the Deaf People in Manauara.